Formulation of a Spray Gel Containing Asiaticoside and Niacinamide Combination for Anti-acne - Nurdianti, Lusi; Gustaman, Firman; Kurniady, Fabillah; Setiawan, Fajar; Firmansya, Ardianes (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Asiaticoside is one of the compounds of the triterpenoid group that functions as an antibacterial by forming a complex with cell membranes that pass through hydrogen bonds, then destroying the permeability of bacterial cell walls. Spray gel is considered a more practical and safer form of gel preparations due to its use, which can minimize microorganism contamination. This study aims to determine the effect of variations in the concentration of asiaticoside combined with niacinamide on its physical properties and antibacterial activity. This research method was carried out experimentally to manufacture spray gel preparations with variations in asiaticoside concentrations of 0%, 1%, 2%, 3%, and 4%. Spray gel preparations were tested for physical properties, stability, and antibacterial activity using the good diffusion method by producing preparations that meet the requirements of physical properties testing, did not cause irritating effects on the skin, good stability and results of antibacterial activity of spray gels produce different inhibitory zone diameters of 1.73 mm ± 2.00 (F0); 5.21 mm ± 1.25 (F1); 6.38 mm ± 1.01 (F2); 12.57 mm ± 4.73 (F3) and 16.20 mm ± 5.04 (F4). The five formulas exhibit good physical properties, stability, and antibacterial activity against Propionibacterium acnes.